ANALYSING FACTORS THAT DRIVE CUSTOMER SATISFACTION OF GO-RIDE MANADO. - Oroh, Felly .; Lapian, S. L. H. V. Joyce; Tumbuan, Willem J.F.Alfa (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Transport plays very vital role in the development of a country’s economy, indetermining overall productivity, quality of life of citizens, access to goods and services and the pattern for distributuion of economic activity. Motorcycle is one of land transport and included in the classification of types of private vehicles but nowadays motorcycles also perform the function of public transport. This kind of transportation is known as Ojek. Currently there are two kinds of ojek services, namely "Offline Ojek" and “Online Ojek". This research analyzed the factor that drive customer satisfaction of Go-ride Manado. Quantitative method is used to collect the data in this research. The sample of this research is 100 customers of Go-Ride in Manado. This research used the Factor Analysis Method. Based on the analysis and discussion, there are 3 main factors that drive consumer satisfaction of Goride in Manado, namely: fisrt, technology & service quality, second, company image and marketing and third, customer service.Keywords: Transport, Goride, Customer Satisfaction, Factor Analysis.